Telegram Bot-Based Expert System as A Detection Tool for Early Symptoms of Borderline Personality Disorder - Lysbeth Venella Oey; Ridwan Sanjaya; FX Hendra Prasetya (Soegijapranata Catholic University, 2023)
The prolonged COVID-19 pandemic may cause stress that leads to both physical and mental health issues, especially for those who categorized as mentally fragile people, such as the people with Borderline Personality Disorder (BPD) where their fragility is caused by overreaction to stress compared to normal people. This journal explains how AI is applied in form of a Telegram-bot based expert system that aims to be a tool to detect early symptoms of BPD and provide treatment advice to people with BPD (PWBPD) as well as people who can potentially be PWBPD, according to recommendation of the psychologist. This research was conducted with qualitative method. The data collection is done by interview and literature study. Application development is carried out using waterfall method, forward chaining reasoning method, PHP, and MySQL. Application testing is done by interview to psychologist. The study shows an overall result that this tool is useful in providing education, detection, and the right ways to treat early symptoms of BPD. This application is also considered interesting and easy to use. The application testing results have been confirmed to pass the qualitative test using interview method with the psychologist and BPD expert, Dr. Christin Wibhowo, S.Psi, M.Si.